MANAJEMEN REKRUTMEN TENAGA PENDIDIK DI SDIT SA’ADIAH KECAMATAN KUBUNG KABUPATEN SOLOK - Maivia Sandela (IAIN Batusangkar, 2019)
This study aims to determine the planning, organizing, implementing, and supervising the recruitment of educators at SDIT Sa’adiah Salayo. This type of research is descriptive qualitative. The informants in the study were the chairman of the foundation, the principal, and the head of the administration of SDIT Sa’adiah Salayo. Data collection techniques through participatory observation, in-depth interviews and documentation studies. Data analysis uses the Miles and Huberman model which divides data analysis into three namely data reduction, data presentation, and drawing conclusions. Data validity testing techniques using data triangulation and method triangulation. The results showed that the management of the recruitment of educators at SDIT Sa'adiah Salayo, began planning the recruitment of educators including: analysis of needs, preparation of recruitment, and determination of recruitment qualifications. Organizing the recruitment of educators also goes well in the process of recruiting new educators at SDIT Sa'adiah Salayo, which always maintains coordinated cooperation with one another from the foundation to the committee for the recruitment of new teaching staff. The recruitment of educators at SDIT Sa'adiah Salayo includes: dissemination of recruitment announcements for educators, acceptance of applications, selection of educators, and decisions on recruitment of educators. As well as conducting good supervision from the foundation and the principal of the recruitment committee, during the recruitment took place at SDIT Sa'adiah Salayo.Keywords: Recruitment Management and Educators.